Energy Analytics for Smart Meter Data using Consumer Centric Approach - K, Nimala; Arasan. R, Thamizh (International Journal of Engineering and Technology, 2018)
A short-range residential consumerâ€™s demand forecasting at the distinct and cumulative level, by an analysis of data using consumer based centric approach. Energy intake behavior might fluctuate among various seasonal factors; the consumed current will change from one season to other. So hereby we are building a model which helps to calculate future electricity consumption data from the obtain ability of past smart meter data. Currently utility companies accumulate the data, use it, share for further practice, and abandon usage data at their discretion, with no input from customers. In many cases, consumers do not even have entree to their own data. But in this project Consumer can have fast admittance and control over their individual data, and also helps to choose the familiar algorithms for the data analyze rather than including third party applications. By end of analyze technique, the analyzed output will be driven to some user interactive application by creating a Graphical User Interface.Â Â